Age, Sex and Body Weight Related Echocardiographic Parameters of Clinically Healthy New Zealand White Rabbits - Dilek, Omer Gurkan; Erden, Hasan (Acta Scientiae Veterinariae, 2019)
Background: Echocardiography provides useful additional information on cardiac dimensions including heart wall and dimension of the ventricles, atria and conditions. Rabbits have been diagnosed with cardiac diseases, and an understanding of the animals’ cardiac chamber dimensions is vital in assessing the diseases’ severity and prognoses. Changes in cardiac dimensions due to age related and body weight were determined at different animals. The increased incidence of congenital cardiovascular anomalies makes it essential to establish the diagnosis at an early age. The aims of this study 1) establish normal values for the commonly used two-dimensional (2D) M-mode parameters using pre anaesthetics and 2) evaluate the effects of age, sex, and body weight on echocardiographic parameters in clinically healthy New Zealand rabbits. Materials, Methods & Results: In this study we used 49 New Zealand white rabbits (25 male, 24 female) all reared under the same conditions. A general physical and clinical examination including complete blood count was performed for each animal. Body surface area was calculated as BSA= 0.00718 × Height 0.725 × Weight 0.425. Rabbits were sedated with midazolam before echocardiographic examination was performed. Echocardiographic examination was performed using a DC 6-Vet® (Mindray, PRC) ultrasonographic device equipped with a micro-convex 8 MHz probe. Right parasternal short-axis view, B-mode and two-dimensional guided M-mode parameters were measured. Echocardiographic measurements were performed using leading-edge-to-leading-edge conventions outlined by the American Society of Echocardiography. Statistical analyses were employed using the SPSS 19.0 program. Sex had no significant effect on the measured echocardiographic parameters except in the case of interventricular septum thickness in diastole values of the three-month-old rabbits. The increase in the left ventricular systolic and diastolic diameters, E- point to septal separation, diastolic aortic root parameters for the three, six, and nine-month-old groups indicated persistent anatomic heart enlargement. However, it was also discovered that the fractional shortening percentage of the left ventricle and diastolic diameters of left atrium:aortic root were unrelated to age and weight. Discussion: New Zealand rabbits are an important model for cardiovascular research, mainly as they are small and relatively inexpensive however large enough to allow anatomical and physiological experiments. Different ages and sizes of New Zealand rabbits showed no significant difference in fractional shortening despite heart enlargement. The ejection fraciton, which can be calculated from the left ventricular dimensions via M-mode echocardiography, is another parameter of cardiac function. Our echocardiograph calculated the ejection fraction automatically using the Teicholz formula. It was further observed that three-month-old rabbits ejection fraction of the left ventricle was higher than that of the six and nine-month-old rabbits. This might indicate the necessity of periodical analysis of echocardiographic parameters. Transthoracic echocardiography can be considered an applicable method for cardiovascular research using a growing rabbit animal model after appropriate adjustments for age, sex and body size. These findings give a better understanding of the functional changes investigated by echocardiography in rabbits and will be helpful when evaluating echocardiographic data in small experimental animals.